Model Pengelolaan Berkelanjutan Kawasan Budidaya Udang Vanname (Litopenaeus vannamei) di Pesisir Kabupaten Mamuju - Huska; Ambo Tuwo; Zainuddin (Pascasarjana Universitas Halu Oleo, 2023)
This study aims to determine the existing condition of the pond area that has the potential for aquaculture, estimate the business feasibility of aquaculture systems, build aquaculture models using dynamic analysis to see the most sustainable aquaculture system, develop dynamic models and simulate various scenarios for sustainable management. The applied aquaculture system was analysed with business feasibility by calculating total cost (TC), total revenue (TR), revenue, R/C and pay back period (PBP). Modelling of sustainable management of Vanname shrimp farming areas is done by formulating scenarios and simulation time and making dynamic models using Stella 9.0.1 software, all scenarios are simulated in a vulnerable time for the next 20 years. The results showed that the most effective cultivation system in 3 sub-districts is a semi-intensive system capable of returning investment or pay back period (PBP) which is about 1.4-1.6 years compared to the traditional system which is about 2.7-3.7 years. The simulation results show that the 3333 scenario in terms of cultivation technology is the best scenario or optimistic scenario to run so that the management of vanname shrimp farming in Mamuju Regency can be sustainable because in the next 20 years most of the cultivation technology will switch from traditional systems to semi-intensive systems. Keywords: Dynamic Model, Business Feasibility, Vanname Shrimp.